2019
DOI: 10.1093/gbe/evz159
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Genome Assembly of a Neotropical Mutualistic Ant

Abstract: The success of social insects is largely intertwined with their highly advanced chemical communication system that facilitates recognition and discrimination of species and nest-mates, recruitment, and division of labor. Hydrocarbons, which cover the cuticle of insects, not only serve as waterproofing agents but also constitute a major component of this communication system. Two cryptic Crematogaster species, which share their nest with Camponotus ants, show striking diversity in their cuticular hydrocarbon (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…In order to carry out evolutionary analyses, we first determined orthology between the proteomes of C. obscurior and 9 further ant species, which we either downloaded from the hymenopteragenome.org website (accessed August 2020; Elsik et al 2015): Atta cephalotes, Pogonomyrmex barbatus, Solonopsis invicta and Wasmannia auropunctata ; or NCBI (accessed August 2020): Monomorium pharaonis, Temnothorax cuvispinosus, Temnothorax longispinosus, Vollenhovia emery . Data for Crematogaster levior were obtained from the authors of the genome publication upon request (Hartke et al, 2019). Orthology was determined with OrthoFinder (Emms and Kelly, 2015) at default settings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to carry out evolutionary analyses, we first determined orthology between the proteomes of C. obscurior and 9 further ant species, which we either downloaded from the hymenopteragenome.org website (accessed August 2020; Elsik et al 2015): Atta cephalotes, Pogonomyrmex barbatus, Solonopsis invicta and Wasmannia auropunctata ; or NCBI (accessed August 2020): Monomorium pharaonis, Temnothorax cuvispinosus, Temnothorax longispinosus, Vollenhovia emery . Data for Crematogaster levior were obtained from the authors of the genome publication upon request (Hartke et al, 2019). Orthology was determined with OrthoFinder (Emms and Kelly, 2015) at default settings.…”
Section: Methodsmentioning
confidence: 99%
“…In order to carry out evolutionary analyses, we first determined orthology between the proteomes of C. obscurior and 9 further ant species, which we either downloaded from the hymenopteragenome.org were obtained from the authors of the genome publication upon request (Hartke et al, 2019). Orthology was determined with OrthoFinder (Emms and Kelly, 2015) at default settings.…”
Section: Molecular Evolution and Selection Analysesmentioning
confidence: 99%
“…Members of the same gene families are involved in the biosynthesis of fatty acids and hydrocarbons (energy storage), which makes it difficult to disentangle these two biosynthetic pathways. Despite several studies in Drosophila ( Dallerac et al 2000 ; Labeur et al 2002 ; Chertemps et al 2006 , 2007 ; Chung et al 2009 , 2014 ; Wicker-Thomas and Chertemps 2010 ; Qui et al 2012 ; Dembeck et al 2015 ; Ng et al 2015 ), genes that are particularly involved in CHC biosynthesis are still largely unknown, especially in insect families in which the involved gene families underwent large gene expansions ( Hartke et al 2019a ; Tupec et al 2019 ). In social insects, and especially ants, CHC profiles are often very complex and can comprise hundreds of different molecules ( Martin and Drijfhout 2009 ; Sprenger and Menzel 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In social insects, and especially ants, CHC profiles are often very complex and can comprise hundreds of different molecules ( Martin and Drijfhout 2009 ; Sprenger and Menzel 2020 ). This is reflected by high numbers of elongases ( Hartke et al 2019a ) and desaturases ( Helmkampf et al 2015 ) found in ants compared to other insect taxa. However, to our knowledge, in ants, there are no functionally validated genes shown to be directly involved in CHC biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometry is a fluorescence-based technique used to detects the intensity of fluorescence emitted by DNA stained with propidium iodide [ 12 ]. As a relatively quick and reliable method for accurately estimate the size of even large genomes, flow cytometry has been widely used to analyze various insect genomes, such as in firefly [ 13 ], the stick insect Clitarchus hookeri [ 14 ], Neotropical mutualistic ant [ 15 ], and Helicoverpa moths [ 16 ]. Nevertheless, the application of flow cytometry is limited by the availability of intact tissue [ 17 ] and the estimate is also affected by chromatin condensation and the proportion of cells in G 0 to G 1 phases.…”
Section: Introductionmentioning
confidence: 99%